2009
DOI: 10.1108/03090590910985408
|View full text |Cite
|
Sign up to set email alerts
|

Providing demonstrable return‐on‐investment for organisational learning and training

Abstract: Purpose -The aim of this paper is to present a holistic approach to training, that clearly demonstrates cost savings with improved effectiveness and efficiencies that are aligned to business objectives.Design/methodology/approach -Extending Kirkpatrick's evaluation framework with Phillips's return-on-investment (ROI) concepts, the paper conveys a number of successes; including trainee satisfaction and the capturing of improved knowledge and skills.Findings -The paper includes case studies of how, and to what e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
7
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 12 publications
2
7
0
Order By: Relevance
“…Four instructional designers, three working in private industry, found that explaining the return on investment helped to persuade clients of the importance of evaluation. This supports the findings conveyed by Elliott et al (2009). One instructional designer working as an external consultant identified storytelling as effective in creating context; the designer described making an analogy about the importance of changing the oil in a new car.…”
Section: Resultssupporting
confidence: 93%
See 2 more Smart Citations
“…Four instructional designers, three working in private industry, found that explaining the return on investment helped to persuade clients of the importance of evaluation. This supports the findings conveyed by Elliott et al (2009). One instructional designer working as an external consultant identified storytelling as effective in creating context; the designer described making an analogy about the importance of changing the oil in a new car.…”
Section: Resultssupporting
confidence: 93%
“…Lack of stakeholder interest in measuring the effectiveness of training and preference for creating new instructional materials were also considered prevalent challenges concerning formative evaluation in government and military environments. This coincides with Elliott et al’s (2009) findings regarding the disconnect between how training departments and their clients or organizations perceive the value of evaluation. The challenges to conducting formative evaluation raised by instructional designers in private industry included creating tools to accurately assess mastery of a nebulous skill, lack of resources (i.e., people and funding), resistance of technical specialists to follow designer instructions, and faculty mistrust of instructional‐designer intent due to lack of understanding the instructional designer's role and expertise.…”
Section: Resultssupporting
confidence: 89%
See 1 more Smart Citation
“…Consistent with the comments of others, this interviewee suggested that the programme should set out at the outset what the measures of success are to be, for instance by adopting the CIRO approach. The CIRO methodology of evaluation -Context, Input, Reaction and Outcome -takes measurements prior to the intervention as well as afterwards (see Elliott et al, 2009). This should permit a "before" and "after" evaluation of programme impact.…”
Section: Costs and Benefitsmentioning
confidence: 99%
“…Trainees' reactions represent the first level of the Kirkpatrick's Hierarchical Model of Training Outcomes (1959a, 1959b, 1960a, 1960b, 1967, as well as of all models aiming at evaluating training (See for example: Warr et al, 1970;Hamblin, 1974;Cannon-Bowers et al, 1995;Kaufman et al, 1995;Cascio, 1999;Phillips, 2003;Pineda, 2010). BEIs have adopted this practice from companies, for which trainees' reactions remain the most (and for a large majority of them the only) used dimension of training evaluation (Long, Dubois and Faley, 2008;Elliott, Dawson and Edwards, 2009). Although extensively used in business education, the collection of students' course evaluations is often experienced as a mere administrative task, with little outcomes and implications.…”
mentioning
confidence: 99%